2011
DOI: 10.1007/s10152-011-0271-2
|View full text |Cite
|
Sign up to set email alerts
|

The fate of an immigrant: Ensis directus in the eastern German Bight

Abstract: We studied Ensis directus in the subtidal (7-16 m depth) of the eastern German Bight. The jackknife clam that invaded in the German Bight in 1978 has all characteristics of a successful immigrant: Ensis directus has a high reproductive capacity (juveniles, July 2001: Amrumbank 1,914 m -2 , Eiderstedt/Vogelsand: 11,638 m -2 ), short generation times and growths rapidly: maximum growth rates were higher than in former studies (mean: 3 mm month -1 , 2nd year: up to 14 mm month -1 ). Ensis directus uses natural me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…However, differences were observed on modelled niches and spatial projections. Limits of the ecological niches modelled with both ENMs (minimum and maximum thermal tolerances and bathymetric preference) do not differ greatly and are consistent with the ecological knowledge of the clam (Cardoso et al 2006(Cardoso et al , 2009Dannheim and Rumohr 2012;Dauvin et al 2007;Dekker and Beukema 2012;Freudendahl et al 2010;Ghertsos et al 2000;Palmer 2004;Vierna et al 2012;Beukema and Dekker 1995). The main differences between NPPEN and MAXENT results are generated by the shape of the ecological niche (fringe of the niche steeper with MAXENT than with NPPEN).…”
Section: Projected Equatorward Expansion Of Ensis Directus In Europesupporting
confidence: 77%
See 1 more Smart Citation
“…However, differences were observed on modelled niches and spatial projections. Limits of the ecological niches modelled with both ENMs (minimum and maximum thermal tolerances and bathymetric preference) do not differ greatly and are consistent with the ecological knowledge of the clam (Cardoso et al 2006(Cardoso et al , 2009Dannheim and Rumohr 2012;Dauvin et al 2007;Dekker and Beukema 2012;Freudendahl et al 2010;Ghertsos et al 2000;Palmer 2004;Vierna et al 2012;Beukema and Dekker 1995). The main differences between NPPEN and MAXENT results are generated by the shape of the ecological niche (fringe of the niche steeper with MAXENT than with NPPEN).…”
Section: Projected Equatorward Expansion Of Ensis Directus In Europesupporting
confidence: 77%
“…No study has reported the disappearance of a native species related to the invasion of E. directus in Europe. Dannheim and colleagues, on the opposite, found that the presence of E. directus favored the settlement of some other deposit feeders (Dannheim and Rumohr 2012). In England, the fishing industry gets interested to harvest the razor clam stocks (the native species E. siliqua and E. arcuatus and the introduced species E. directus) as food source for human consumption (Pyke 2002).…”
Section: Projected Equatorward Expansion Of Ensis Directus In Europementioning
confidence: 99%
“…Inspection of important spots used by the tagged birds revealed that herring gulls from Oland visited razor clam beds in the intertidal zone, although these were only available to herring gulls for a short time during low tide. Razor clams were accidently introduced to the Wadden Sea with ballast water in 1978 (Dannheim & Rumohr, 2012; Freudendahl, Nielsen, Jensen, & Jensen, 2010; von Cosel, Dörjes, & Mühlenhardt‐Siegel, 1982), and the species has since extended its range substantially over the last three decades (Dekker & Beukema, 2012). Common eiders, common scoters, and various shorebird and gull species regularly use this new source of food (Swennen, Leopold, & Stock, 1985; Tulp et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, no studies have been published so far that support a suppression of native species by E. directus in European waters. Quite the opposite, both Armonies and Reise (1999) and Dannheim and Rumohr (2011) concluded that the newcomer might have favoured the appearance of some other species in the areas in which it occurs. Nowadays, E. directus is a commercial species in Europe (see Marine Stewardship Council 2012).…”
Section: Introductionmentioning
confidence: 99%